2019
DOI: 10.3390/healthcare7030088
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Dietary and Nutrient Intake on Gynecologic Cancers

Abstract: The contribution of diet to cancer risk has been considered to be higher in advanced countries than in developing countries. In this paper, I review the current issues (a review of the relevant literature), and the effects of the dietary and nutrient intake on three types of gynecologic cancer (cervical, endometrial and ovarian cancers). In cervical cancer, the most important roles of diet/nutrition in relation to cancer are prophylaxis and countermeasures against human papillomavirus (HPV) infection. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 173 publications
0
44
0
3
Order By: Relevance
“…In a hospital-based case–control study, on the other hand, serum levels of retinol were not inversely associated with the risk of cervical cancer [ 17 ]. Therefore, retinol (vitamin A) may inhibit the early events (HPV infection and CIN 1 development) of cervical carcinogenesis [ 18 ].…”
Section: Nutrientsmentioning
confidence: 99%
“…In a hospital-based case–control study, on the other hand, serum levels of retinol were not inversely associated with the risk of cervical cancer [ 17 ]. Therefore, retinol (vitamin A) may inhibit the early events (HPV infection and CIN 1 development) of cervical carcinogenesis [ 18 ].…”
Section: Nutrientsmentioning
confidence: 99%
“…Most recently, we reviewed the recent clinical studies of dietary oxidants on development of cervical cancer [34]. The following were established in the results.…”
Section: The Effects Of Dietary Antioxidants On the Development Of Cementioning
confidence: 99%
“…Previous studies have confirmed that dietary factors, vitamin A, in particular, is closely related to decreased HPVassociated tumors (cervical cancer, squamous cell cancers of the head and neck, and prostate cancer) [15][16][17][18]. However, findings from former studies regarding the relationship between vitamin A and HPV infection were limited [19,20]. Since the cancer risk of HPV infection has been affirmed, it is necessary to study the association between vitamin A and HPV infection from the perspective of preventing such tumors.…”
Section: Introductionmentioning
confidence: 99%